Relationship between External Morphology and Gonads in Rainbow Lizard (Agama agama) in Obafemi Awolowo University, Ile-Ife, Nigeria - , A. O. Bamidele; , E. O. Mayor (Archives of Current Research International, 2020)
Background of the Study: The morphology of any reptile may be affected by different environmental factors such as climate change and habitat related features such as availability of food and other resources. Objective: This study aimed at determining the morphology and sexual variation of Rainbow male and female lizards (Agama.agama) in Obafemi Awolowo University. Study Design: Three locations in the University were selected (Student Hostels, Academic Area and Staff Quarters) and rainbow lizards were sampled from June to December 2019. Results: A total of 93 lizards were sampled, body parameters were measured, and the gonads were weighed after dissection. There was a positive correlation (0.98 & 0.78) between the body weight and gonad weight of the male and female lizards in all the three locations. Also, the specimen from the academic area of the University had the least body and gonad weight, while the samples caught in the staff quarters had the highest body and gonad weight. The Principal Component Analysis (PCA) showed a relationship in the body and gonad weight with few differences from samples captured in the academic area. Conclusion: In summary, external morphology of the rainbow lizards from all the three locations were similar with little difference in body weight. There was a positive relationship between external morphology and gonads of rainbow lizards.